Qualitative evaluation of TAMARPP, the relapse prevention program for substance abusers at the Mental Health and Welfare Center - Taniai, Tomoko; Yottsuji, Naomi; Okuda, Hidemi; Karibe, Haruo; Miura, Kasumi; Hiraga, Masasi; Kondo, Ayumi; Matsumoto, Toshihiko (Nihon Arukoru Yakubutsu Igakkai zasshi = Japanese journal of alcohol studies & drug dependence, 2014)
The development of an effective treatment system for patients with addiction-related problems like substance abuse or pathological gambling is urgently needed. The purpose of this study was to clarify the therapeutic factors of the Tama Mental Health and Welfare Center Relapse Prevention Program (TAMARPP). The program is provided at the Tama Comprehensive Center for Mental Health and Welfare, which is operated publicly by the Tokyo Metropolitan Government. Seven personnel (3 clinical psychologists, 2 public health nurses, and 2 recovering counselors) searched the consultation records of 31 participants who had continued treatment longer than 1 year, and made a list of qualitative factors that may positively impact participant outcome. The following six factors were extracted: 1) a "no-blame" atmosphere that makes participants feel safe and free; 2) a mutual helping process that enables participants to empathize with one another; 3) an individual-centered approach that focuses on a participant's motivation to recover; 4) a psycho-educational process that establishes treatment goals; 5) a treatment goal that involves some type of social role; and 6) the referral of graduates to another long-term treatment program such as Narcotics Anonymous. Our results suggest the need of personnel to provide treatment as follows: 1) keep the circumstances safe; 2) use a method that matches the participant's motivation; 3) refer graduates to another in-depth treatment program; 4) emphasize the relationship between thinking, emotion, and behavior; and 5) improve the quality of life of the participant. The missions of our center, an official institution that runs such a program, are as follows: 1) to be the first place at which addicts seek aid during the early stage; 2) to cooperate with other facilities in order to provide social resources that support recovery; and 3) to support patients suffering from both addiction and comorbid psychiatric diseases.